Solve for \( y \). \[ 2 y^{2}+11 y+5=(y+5)^{2} \] If there is more than one solution, separate them with commas.
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the equation \( 2y^{2} + 11y + 5 = (y + 5)^{2} \), we first expand the right-hand side: \[ (y + 5)^{2} = y^{2} + 10y + 25 \] Now we have the equation: \[ 2y^{2} + 11y + 5 = y^{2} + 10y + 25 \] Next, we can rearrange and combine like terms by moving everything to one side of the equation: \[ 2y^{2} + 11y + 5 - y^{2} - 10y - 25 = 0 \] This simplifies to: \[ y^{2} + y - 20 = 0 \] Now we can factor the quadratic equation: \[ (y + 5)(y - 4) = 0 \] Setting each factor equal to zero gives us the solutions: \[ y + 5 = 0 \quad \Rightarrow \quad y = -5 \] \[ y - 4 = 0 \quad \Rightarrow \quad y = 4 \] Thus, the solutions to the equation are: \[ y = -5, 4 \]